Facets of Graffiti Art and Street Art Documentation Online: A Domain and Content Analysis - (:unkn) unknown (My University, 2018)
In this dissertation research I have applied a mixed methods approach to analyze the documentation of street art and graffiti art in online collections. The data for this study comes from the organizational labels used on 241 websites that feature photographs of street art and graffiti art, as well as related textual information provided on these sites and interviews with thirteen of the curators of the sites. The goal of the research is to demonstrate the existence of a coherent domain of street art and graffiti art documentation that may in turn be used to inform the formal design of systems to record evidence of the art movement and the works. Open coding was applied to the organizational text used by the websites to reveal a set of four categories of descriptive facets. The categories are related to general aspects of the websites themselves, the supports upon which works are created or placed, the various types of works, and location information. There are several facets included within each of these four categories. When a website shared information about the site itself, most frequently on an about sub-page, this was analyzed for audience, explicit organization methods, motivations for creating the site, and art style vocabulary used. Audience and explicit organization methods were rarely shared. Motivations were coded as internal, external, or mixed with emphasis on internal or external. Art style vocabulary varies and is tied to motivations, but the most commonly named style is graffiti or a variant thereof. Sites that feature work from internally motivated sites feature the widest variety of art style terminology and tend to avoid use of graffiti and graffiti-related terms. All website curators that could be contacted were offered the opportunity to participate in an interview regarding website organization for graffiti art and street art. Thirteen interviews were conducted: one by phone, one by Skype, and eleven by email. The interview data reveals varying opinions on what terminologies or categories should be used to organize photographic collections of graffiti art and street art online, but there is general agreement that the name of the artist or crew (if known), the year of the work, and the location of the work are the most important facets. The curators demonstrate that the size of the collection, geographic focus, and scope of works featured will have an impact on how the site should be organized. The ontological formation of the domain of street art and graffiti art documentation is evidenced by the combined results of the website analyses and interviews.
Keywords: Art Documentation; Domain Analysis; Graffiti; Information Organization; Knowledge Organization; Street Art